Postgraduate Students' Recruitment Strategies in Higher Education Institutions of Malaysia - Isa, Filzah Md; Othman, Siti Norezam; Muhammad, Nik Maheran Nik (International Review of Management and Marketing, 2016)
Almost every higher education institution in the world is facing a tough challenge to recruit new students especially the talented ones due to intense competition in the local and global market. The institution needs to design effective marketing strategies that able to recruit students. The recruitment strategies in public higher education institutions can be classified into three main categories namely; non-active recruiting strategy, passive recruiting strategy, and active recruiting strategy. This study reveals that non-active recruitment strategies such as reputation of the university, and passive recruitment strategies such as advertisements have significant relationships with the talented postgraduate students' recruitment. However, active recruitment strategies (i.e. travelling abroad to recruit students) were not significantly correlated to talented postgraduate recruitment. Research Universities (i.e. USM, UM, UKM, UPM and UTM), seem to have more quality students as compared to other non-Research Universities except for the UIAM. Thus to be more effective, the recruitment of postgraduate student strategies and practices in the public universities needs to be reviewed continuously since the needs and wants of the students are ever changing. Keywords: Recruitment strategy, marketing strategy, higher education institutions, quality students JEL Classifications: 123, M31